2019
DOI: 10.1016/j.ebiom.2019.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nwd1 activity attenuates neuronal hyperexcitability and GluN2B phosphorylation in the hippocampus

Abstract: Background: NACHT and WD repeat domain-containing protein 1 (Nwd1) is a member of the innate immune protein subfamily. Nwd1 contributes to the androgen receptor signaling pathway and is involved in axonal growth. However, the mechanisms that underlie pathophysiological dysfunction in seizures remain unclear. Methods: Biochemical methods were used to assess Nwd1 expression and localization in a mouse model of kainic acid (KA)-induced acute seizures and temporal lobe epilepsy (TLE) patients. Electrophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…A physiological link exists between physical frailty and cognitive decline. These underlying processes include chronic inflammation, impaired hypothalamic-pituitary axis stress response, imbalanced energy metabolism, mitochondrial dysfunction, oxidative stress, and neuroendocrine dysfunction (Freitas et al, 2019 ; Adams et al, 2019 ; Yang et al, 2019 ; Ma and Chan, 2020 ). Blood-based biomarkers for CI are very important and can be effectively used to promote healthy brain aging, for screening and diagnosis at every stage of the dementias, assessment of risk to the disease, and may also be helpful in drug discovery approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A physiological link exists between physical frailty and cognitive decline. These underlying processes include chronic inflammation, impaired hypothalamic-pituitary axis stress response, imbalanced energy metabolism, mitochondrial dysfunction, oxidative stress, and neuroendocrine dysfunction (Freitas et al, 2019 ; Adams et al, 2019 ; Yang et al, 2019 ; Ma and Chan, 2020 ). Blood-based biomarkers for CI are very important and can be effectively used to promote healthy brain aging, for screening and diagnosis at every stage of the dementias, assessment of risk to the disease, and may also be helpful in drug discovery approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are characterized by progressive neurodegeneration and injury closely related to aging, including PD, Alzheimer's disease (AD), amyotrophic lateral sclerosis, et cetera. Although the pathogenesis of neurodegenerative diseases varies, they still share many common pathogenic features and mechanisms, such as misfolded protein aggregation, neuronal apoptosis, synaptic loss, neurotransmitter abnormalities, et cetera ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…gene have not been reported to date, it was recently shown that the neuronal expression of NWD1 is upregulated in patients with temporal lobe epilepsy (Yang et al, 2019).…”
Section: Implication Of Nwd1 and Purinosome Components In Neurologicamentioning
confidence: 99%
“…Using a mouse model of acute epileptic seizures, it was suggested that Nwd1 regulates the neuronal hyperexcitability of glutamatergic synaptic transmission in the adult brain (Yang et al, 2019). Therefore, Nwd1 might be involved in a novel mechanism of regulation of the synaptic transmission via the formation of purinosomes or other macromolecular complexes.…”
Section: Implication Of Nwd1 and Purinosome Components In Neurologicamentioning
confidence: 99%